2020
DOI: 10.1155/2020/4865614
|View full text |Cite
|
Sign up to set email alerts
|

Transcutaneous Electrical Stimulation and Dysphagia Rehabilitation: A Narrative Review

Abstract: Transcutaneous electrical stimulation (TES) was introduced as a modality for dysphagia rehabilitation more than a decade ago. The underlying premise of this modality is improving the structural movements and enhancing neural activation based on stimulation-induced muscle contractions. However, divisive evidence exists regarding the effectiveness of this treatment modality. This manuscript reviews current evidence regarding the effects of transcutaneous electrical stimulation (TES) on clinical and physiological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…This may not be enough time for CNS to provide adaptation responses to a new perturbation. Future studies are encouraged to test the physiologic effect of TES with an additional number of swallowing trials (i.e., [15][16][17][18][19][20] to better monitor the adaptation of swallowing motor activity to external perturbation from TES.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This may not be enough time for CNS to provide adaptation responses to a new perturbation. Future studies are encouraged to test the physiologic effect of TES with an additional number of swallowing trials (i.e., [15][16][17][18][19][20] to better monitor the adaptation of swallowing motor activity to external perturbation from TES.…”
Section: Discussionmentioning
confidence: 99%
“…Transcutaneous electrical stimulation was primarily purported to strengthen the weaker muscles and re‐educate safe swallowing 15,16 . However, despite significant clinical studies that have been conducted regarding the efficacy of TES on dysphagia treatment, the findings are still inconclusive 17 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, use of sensory versus motor NMES resulted in improved clearance of pharyngeal residue and timeliness in swallow, ultimately resulting in improved scores on the PAS [ 11 ]. Improvements in swallow cannot be solely attributed to electrical stimulation as standard of care dysphagia therapy was provided during this time frame [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported equivocal evidence regarding the clinical effect of TES on swallowing 1 . While some potential reasons for these controversial reports might be related to research designs of differing rigor, the applied TES protocol or the type of therapy paired with TES, 2,3 the primary limitation may relate to our lack of understanding regarding the effect of TES on swallowing physiology. Understanding the effect of TES parameters on swallowing physiology will help us depict a more comprehensive picture of the benefits and limitations of TES in swallowing rehabilitation.…”
Section: Introductionmentioning
confidence: 99%